The requirement of information availability under the E-Commerce Act 2006 - Zulhuda, Sonny (Cyber Security Malaysia, 2009)
One of the key components in information security is the information availability, which seeks to ensure that authorized users have access to information and associated assets whenever required. This availability factor is so important to the extent that its deficiency can adversely affect other aspects of information security, namely the integrity and confidentiality of information.